Chestnuts and by-products as source of natural antioxidants in meat and meat products: A review. (December 2018) - Echegaray, Noemí; Gómez, Belén; Barba, Francisco J.; Franco, Daniel; Estévez, Mario; Carballo, Javier; Marszałek, Krystian; Lorenzo, Jose M.
Abstract: Background: Chestnuts have traditionally been used for both human and animal consumption due to their nutritional properties. During chestnut industrial processing, several by-products are generated, like chestnut wood, flowers, leaves, shells, barks and burs. These by-products constitute an important source of antioxidant compounds, which can be used as food additives to be incorporated in other food products such as meat in order to improve nutritional and quality characteristics as well as to delay oxidation processes. Scope and approach: This systematic literature review evaluated the main antioxidant compounds of chestnuts by-products, including total content and profile. Moreover, the impact of chestnut by-products addition on animal diet in the microbiological, physicochemical and sensorial properties of meat products will be reported. Finally, the effects of the use of chestnut by-products extracts on the quality and oxidative stability of meat products will be also evaluated. Key findings and conclusions: According to literature, chestnut by-products may also provide beneficial effects on health, being involved in the prevention of noncommunicable diseases. At this stage of development, there is a need to carry out more specific studies about the antioxidant profile of the extracts obtained from chestnut by-products. Further research is needed to i) optimize extraction of bioactive compounds, ii) establish effective and safe doses and iii) clarify their effects on microbial inactivation, nutritional, bioactive, physicochemical and sensorial properties of the new meat products. Moreover, further in vivo (animal and human) assays are necessary in order to evaluate the potential health-promoting benefits of extracts obtained from chestnuts by-products. Highlights: Chestnuts by-products are an important source of bioactive compounds. Phenolic acids, flavonoids and tannins are the most abundant presented in chestnuts. Chestnuts by-products are a good alternative to replace the use of the artificial antioxidants.